Nonessential amino acid usage for protein replenishment in humans: a method of estimation - Tessari, Paolo (The American journal of clinical nutrition, 2019)
Essential amino acids (EAAs) are key factors in determining dietary protein quality. Their RDAs have been estimated. However, although nonessential amino acids (NEAAs) are utilized for protein synthesis too, no estimates of their usage for body protein replenishment have been proposed so far. The aim of this study was to provide minimum, approximate estimates of NEAA usage for body protein replenishment/conservation in humans. A correlation between the pattern of both EAAs and NEAAs in body proteins, and their usage, was assumed. In order to reconstruct an “average” amino acid pattern/composition of total body proteins (as grams of amino acid per gram of protein), published data of relevant human organs/tissues (skeletal muscle, liver, kidney, gut, and collagen, making up ∼74% of total proteins) were retrieved. The (unknown) amino acid composition of residual proteins (∼26% of total proteins) was assumed to be the same as for the sum of the aforementioned organs excluding collagen. Using international EAA RDA values, an average ratio of EAA RDA to the calculated whole-body EAA composition was derived. This ratio was then used to back-calculate NEAA usage for protein replenishment. The data were calculated also using estimated organ/tissue amino acid turnover. The individual ratios of World Health Organization/Food and Agriculture Organization/United Nations University RDA to EAA content ranged between 1.35 (phenylalanine + tyrosine) and 3.68 (leucine), with a mean ± SD value of 2.72 ± 0.81. In a reference 70-kg subject, calculated NEAA usage for body protein replenishment ranged from 0.73 g/d for asparagine to 3.61 g/d for proline. Use of amino acid turnover data yielded similar results. Total NEAA usage for body protein replenishment was ∼19 g/d (45% of total NEAA intake), whereas ∼24 g/d was used for other routes. This method may provide indirect minimum estimates of the usage of NEAAs for body protein replacement in humans.